The use of information by the policy-makers in Malaysia and their awareness of the library and information services / Raja Abdullah Yaacob and Laili Hashim - Yaacob, Raja Abdullah; Hashim, Laili (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
This study explores how information is used by policy-makers in Malaysia and their awareness of information and information services. A survey administered to 400 top government officers involved in policy making and, policy formulation, attempts to identify the policy-makers; elicit the types of policies; the role of information in policy-making and formulation; the types and forms of information used; methods of information usage: types of information provided; the policy-makers' awareness of library and information services; and the dissemination of information in the future. Findings regarding the use of information and the role of information, especially those related to the country, show that information is very important and necessary for effective decision-making. There is also an awareness of the need for increased computerized services. Although there is an awareness of the importance of libraries and information centres, more concerted effort should be made to market and increase the potential of information so that the information needs of the policy-makers could be met.